A Comparative Clinico-Pathological Study On CRP Positive Patients W.S.R. To Amavata (Rheumatoid Arthritis) And Its Management With Vatari Guggulu And Pathyadi Churna - Quazi, Mohammed Faisal; Panda, Pradip Kumar; Das, Arun Kumar; Nayak, Utkalini (International Research Journal of Ayurveda & Yoga, 2021)
Introduction- C-Reactive Protein (CRP) is an acute-phase of inflammatory protein, a highly conserved plasma protein that is named for its reaction with the capsular C-polysaccharide of Pneumococcus. It is an Annular (Ring-shaped) Pentameric protein found in blood plasma, whose circulating concentration rise in response to inflammation and of hepatic origin that increases interleukin-6 secretion by macrophages and T-cells. Due to this type of inflammatory changes there are stiffness, Pain, Swelling of joints along with generalized symptoms of fever etc. present in the disease like Amavata (Rheumatoid Arthritis). Materials and methods- 30 patients of Group-A (15) and Group-B (15) patients were registered from OPD and IPD of Govt. Ayurvedic College & Hospital, Balangir presented with Subjective Parameter as Sandhi Ruja, Sandhi Shotha, Sandhi Stabdhata, Jwara, Aruchi and Daurbalya and Objective Parameter as CRP>6mg/L, ESR, Hb%, DLC,TLC and Lipid profile test. After diagnosis they were under trial with Ayurvedic formulations of Vatari guggulu given 500mg thrice daily after food in Group A and Pathyadi Churna given 5gm twice daily after food with ushnajala for a period of 30 days with respectively. The subjective and objective parameters were assessed in 10 days interval to interpret the result by statistical evaluation. Observation and results:- It has been observed that the result of trial drug Group-A patients is Significant (p<0.05) to reduce both Subjective and Objective parameter after 30 days of treatment as campair to Group-B patients. Conclusion- CRP positive patients suffered from Amavata (Rheumatoid Arthritis) showed Significant improvement after receiving the Ayurvedic formulation ‘Vatari Guggulu’ in this study. No adverse effect was observed.